2018
DOI: 10.1038/nature25445
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Runx3 programs CD8+ T cell residency in non-lymphoid tissues and tumours

Abstract: In this Letter, owing to errors introduced during the proofreading process, the words 'infection with' were missing from the sentence "Furthermore, Runx3 RNAi also impaired T RM cell differentiation in the context of a localized infection with enteric Listeria monocytogenes expressing GP 33-41 (LM-GP 33-41) (Fig. 2b). " In addition, in Fig. 1a, the x-axis label for the bottom right graph should have read "Expression change log 2 (D7 kid/D7 T CM)" rather than "Expression change log 2 (D35 kid/D35 T CM)". In Fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Finally, since a previous study demonstrated an essential role of Runx3 for promoting memory cell formation ( 18 , 46 ), we investigated the impact of MAZR- and/or Runx3-deletion on the generation of memory precursor (MP) CTLs. For this, we examined KLRG1 and CD127 expression patterns of the mutant CTLs, which allows us to identify KLRG1 – CD127 + MP and KLRG1 + CD127 – terminal effector (TE) CTLs ( 5 , 8 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, since a previous study demonstrated an essential role of Runx3 for promoting memory cell formation ( 18 , 46 ), we investigated the impact of MAZR- and/or Runx3-deletion on the generation of memory precursor (MP) CTLs. For this, we examined KLRG1 and CD127 expression patterns of the mutant CTLs, which allows us to identify KLRG1 – CD127 + MP and KLRG1 + CD127 – terminal effector (TE) CTLs ( 5 , 8 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the 21 postnatal-specific TFs are associated with specialized functions, such as immune system development, response to stress, and response to the chemical. For example, RUNX3 plays important roles in the B-cell proliferation ( 26 , 27 ) and T-cell development ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…The DEGseq was used to analyze the differentially expressed genes. To confirm the characteristics of induced T RM , we compared the T RM -related genes previously reported in various mouse models (24)(25)(26)(27)(28)(29). The result showed that the expressions of Itgae, Cd69, Nr4a1 (Nur77), Nr4a2, Ctla4, Cdh1, Cd244, Prdm1, Rgs, Fabp5, and Bhlhe40 are up-regulated, and S1pr1, Ccr7, Sell, and Hnf1a were down-regulated in induced CD8 + T RM (Fig.…”
Section: Long-lived Cd103 + Cd69 + T Rm Cells In Skin Induced By Allo...mentioning
confidence: 92%